The Pandemic is also an Opportunity – About Positive Individual and Social Change - Zbyrad, Teresa (Roczniki Nauk Społecznych, 2023)
The negative effects of the pandemic are widely noted. However, like any social phenomenon, the pandemic, in addition to negative effects, also brought positive effects. However, the latter have a smaller scale, but paradoxically they are of great value for the individual and the family. In my article, I will focus on the positive side, showing the pandemic in a completely different light, which for many people, apart from the destructive power of devastation, has become a chance for change – a positive one. Can a pandemic be an opportunity? Could the evil that came with the virus, decimating humanity, bringing death and suffering to millions of people, causing fear could this evil have produced any good? Could this total and global crisis in the social, economic, professional, family and personal dimensions translate into the strengthening, reconstruction, reconstruction and development of identity? These are the questions I will try to answer.